STUDY OF PERIODONTAL TISSUE STATUS IN PATIENTS WITH PERI-IMPLANTITIS - Adubetska, A.Y.; Shnaider, S.A.; Skulska, S.V.; Anisimov, M.V.; Vyshnevska, H.O.; Malekh, N.V.; Kryvchuk, O.A. (World of Medicine and Biology, 2023)
The study was devoted to researching the condition of the status of periodontal tissues in patients with peri-implantitis. 67 patients with peri-implantitis aged between 25 and 55 years took part in the research. All patients underwent a comprehensive examination of the main disease and dental status according to a single scheme. The dental examination was carried out in a dental office. The comprehensive analysis of the index assessment of periodontal tissues in patients diagnosed with peri-implantitis reveals a pronounced deterioration in periodontal health compared to the average indicators among the 30–50 years old demographic in Ukraine. These data are the basis for the development and implementation of a medical and preventive complex aimed at helping the patients with peri-implantitis.
Keywords: periodontal tissues; oral health; implants; inflammatory disease; adult patients